Fundamentals of signal processing in metric spaces with lattice properties algebraic approach - Popoff, Andrey (CRC Press, Taylor & Francis Group, 2018)
Exploring the interrelation between information theory and signal processing theory, the book contains a new algebraic approach to signal processing theory. The book discusses the methodology of synthesis and analysis of signal processing algorithms providing qualitative increase of signal processing efficiency under parametric and nonparametric prior uncertainty conditions. Examples are included throughout the book to further emphasize new material.